A Chemical-Biological-Radio-Nuclear (CBRN) Filter can be Added to the Air-Outflow Port of a Ventilator to Protect a Home Ventilated Patient From Inhalation of Toxic Industrial Compounds - Be’eri, Eliezer (Disaster Med Public Health Prep, 2018)
OBJECTIVES: Chemical-biological-radio-nuclear (CBRN) gas masks are the standard means for protecting the general population from inhalation of toxic industrial compounds (TICs), for example after industrial accidents or terrorist attacks. However, such gas masks would not protect patients on home mechanical ventilation, as ventilator airflow would bypass the CBRN filter. We therefore evaluated in vivo the safety of adding a standard-issue CBRN filter to the air-outflow port of a home ventilator, as a method for providing TIC protection to such patients. METHODS: Eight adult patients were included in the study. All had been on stable, chronic ventilation via a tracheostomy for at least 3 months before the study. Each patient was ventilated for a period of 1 hour with a standard-issue CBRN filter canister attached to the air-outflow port of their ventilator. Physiological and airflow measurements were made before, during, and after using the filter, and the patients reported their subjective sensation of ventilation continuously during the trial. RESULTS: For all patients, and throughout the entire study, no deterioration in any of the measured physiological parameters and no changes in measured airflow parameters were detected. All patients felt no subjective difference in the sensation of ventilation with the CBRN filter canister in situ, as compared with ventilation without it. This was true even for those patients who were breathing spontaneously and thus activating the ventilator’s trigger/sensitivity function. No technical malfunctions of the ventilators occurred after addition of the CBRN filter canister to the air-outflow ports of the ventilators. CONCLUSIONS: A CBRN filter canister can be added to the air-outflow port of chronically ventilated patients, without causing an objective or subjective deterioration in the quality of the patients’ mechanical ventilation. (Disaster Med Public Health Preparedness. 2018;12:739-743)